2000
DOI: 10.1590/s1516-89132000000400008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low salinity on teredinids

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
11
1
1
Order By: Relevance
“…Finally, surveys by JUNQUEIRA et al (1989) and showed N. reynei to be absent from diverse localities along the Rio de Janeiro coast, although 10 other shipworm species were found. In a later study at one of these localities, Ilha Grande Bay, BARRETO et al (2000) found 11 species of Teredinidae but N. reynei remained absent. and these values are very similar to those at Ajuruteua beach, possibly indicating the harsher environmental conditions of beach habitats.…”
Section: Resultsmentioning
confidence: 89%
“…Finally, surveys by JUNQUEIRA et al (1989) and showed N. reynei to be absent from diverse localities along the Rio de Janeiro coast, although 10 other shipworm species were found. In a later study at one of these localities, Ilha Grande Bay, BARRETO et al (2000) found 11 species of Teredinidae but N. reynei remained absent. and these values are very similar to those at Ajuruteua beach, possibly indicating the harsher environmental conditions of beach habitats.…”
Section: Resultsmentioning
confidence: 89%
“…From this, it can be suggested that the Envigne Valley during the Cenomanian corresponded to an estuarine to intertidal littoral environment, probably not exceeding more than several dozen metres water depth, and with a water salinity scoring between 15% and 25% (for specific rates per species see Saraswathy & Nair ; Barreto et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…(TURNER, 1966) and oceanographic conditions, mainly temperature and salinity (BORGES et al, 2014b;PATI et al, 2014). These conditions affect the survival (BARRETO et al, 2000) and also the activity of endosymbiont bacteria (DISTEL et al, 2002;HORAK;MONTOYA, 2014;TRINDADE-SILVA et al, 2009), thus also affecting the rate and amount of wood consumption.…”
Section: Differences In the Distribution And Abundance Of Teredinidaementioning
confidence: 99%
“…While in Rio de Janeiro the most common method is the use of artificial collectors (BARRETO et al, 2000;JUNQUEIRA et al, 1989;JUNQUEIRA et al, 1991;SILVA et al, 1988;VAROTTO;BARRETO, 1998), in São Paulo direct sampling in mangrove forests is common, despite some use of artificial collectors (LOPES; NARCHI, 1993;LOPES et al, 2000;MORAES et al, 2015). This leads to some differences in research results as regards the composition and abundance of species, beyond the effects of the differences in oceanographic conditions between regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation